Peculiar Ways of Transforming Inflation in to Target Mode - Turaboy, Karaliyev; Maqsud, Rustamov; Baxodir, Usmonov; Aziza, Tursunova (International Journal of Psychosocial Rehabilitation, 2020)
Today, the world economy is changing rapidly. At the same time, in order to gain a foothold, there is always a need for active economic growth and production of competitive goods. It faces various challenges in developing the economy. These are inflationary processes that result from price instability and, as a result, an increase in money demand in the economy.